Review Kurikulum Pendidikan Cara Belajar Siswa Aktif (CBSA) Tahun 1984 dalam Pendidikan Indonesia - Wardhana, Ivan Prapanca (Universitas Veteran Bangun Nusantara, 2021)
Curriculum is an essential thing in the implementation of education. Curriculum changes over time are not without clear reasons and foundations, because these changes are driven by the desire to continuously improve, develop, and improve the quality of national education. The National Education Curriculum has undergone changes from 1947 to 2006. The change is a logical consequence of changes in the political, economic and science and technology systems, socio-cultural, in national and state societies. Curriculum 1984 carries the Skill Approachprocess. Although it prioritizes the approach of the process, but the goal factor remains important, this curriculum is also often called